2010
DOI: 10.1111/j.1365-277x.2010.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral nutrition for patients with advanced ovarian malignancy

Abstract: Background:  Parenteral nutrition (PN) in patients with disseminated ovarian cancer remains controversial. The role of PN in providing nutrition and improving quality of life is unclear. The present study aimed to determine the pattern of prescribing in a large teaching hospital, and to identify subgroups where the use of PN was justified. Methods:  Sixty‐five patients with advanced ovarian carcinoma received PN between January 2002 and May 2008. A retrospective case note review was undertaken to retrieve data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
(36 reference statements)
0
18
0
1
Order By: Relevance
“…Prognostic models for estimating survival are often imprecise and error prone, but a recent study suggests that simple tools based on performance status may serve as reliable indicators of survival 33 . Most reports pertaining to PN administration in palliative care use a Karnofsky performance status index of 50 or higher as a guide for determining eligibility for PN therapy 2 , 15 , 23 , 34 , 35 Table 9.2. provides detail regarding the use of the Karnofsky Performance Scale, which is designed for use with patients aged 16 years and older 36 .…”
Section: Question 9: Is Pn Appropriate For Patients In Palliative Care?mentioning
confidence: 99%
“…Prognostic models for estimating survival are often imprecise and error prone, but a recent study suggests that simple tools based on performance status may serve as reliable indicators of survival 33 . Most reports pertaining to PN administration in palliative care use a Karnofsky performance status index of 50 or higher as a guide for determining eligibility for PN therapy 2 , 15 , 23 , 34 , 35 Table 9.2. provides detail regarding the use of the Karnofsky Performance Scale, which is designed for use with patients aged 16 years and older 36 .…”
Section: Question 9: Is Pn Appropriate For Patients In Palliative Care?mentioning
confidence: 99%
“…It has been found that organisations still repeatedly fail to provide people with the basic right to food, drink and support when they need it [1]. In acknowledgment that food service in hospitals must be given a higher priority and recognised as an integral part of the patient's treatment and care, Irish hospitals must now have a system to evaluate nutrition and hydration care for patients admitted to hospital [2,3]. The purpose of this audit was to examine the level of mealtime support available to patients during the main mealtime service.…”
mentioning
confidence: 99%
“…This accelerates muscle protein loss and is one of the multifactorial causes of sarcopenia [2]. In a systematic review Tsien et al [3] recommended a 50g carbohydrate late evening snack to minimise gluconeogenesis and preserve muscle mass. This has been adopted into clinical guidelines [4].…”
mentioning
confidence: 99%
See 2 more Smart Citations